Evaluation of the Consistency Between Clinical and Preclinical Observers in the Formation of the History Taking Skills of Fourth Year Medical Students of Marmara University - UZUNER, ARZU; AKMAN, MEHMET; APAYDIN KAYA, MEMNUNE ÇİĞDEM; ÇİFÇİLİ, SALİHA SERAP (ORTADOGU AD PRES & PUBL CO, 2011)
Objective: The aim of the present study was to investigate the level of consistency between clinical and preclinical medical observers while evaluating the medical history taking skill of medical students. Material and Methods: Causal comparative survey model is used in this study. A total of 40 students were randomly selected from the fourth year medical students by using the random numbers chart. The Oral History Taking Evaluation Guideline (OHTEG) developed by the researchers and reconciled on in terms of language and context, was used for the evaluation process. The student and patient interviews were evaluated in the internal medicine, family practice and general surgery outpatient clinics by four different observer teams each consisting of one randomly selected preclinial and one clinical observers. Patients presenting for the first time and accepting to take part in the study were admitted to the interview room in the order of presentation. The duration of the interview between students and patients was previously set as 10 minutes. Results: Among the medical students taking part in the study, 17 (42.5%) were males. A weak but significant consistency was observed between the global evaluation points asssigned by the individual observers (k: 0.27, p= 0.001). A weak to good level of consistency was observed in the six subcontents of the Oral History Taking Evaluation Guideline (OHTEG), including the introduction, history of drug use, smoking habits and alcohol intake, family history, system query and the fluency of the interview (k: 0.24, 0.28, 0.53, 0.18, 0.38, 0.35, respectively; p< 0.05). Conclusion: A strong consistency was not observed between clinical and preclinical medical observers while evaluating the medical history taking skill of medical students. This suggests that the priorities of the clinical and preclinical medical observers are different from each other. The sharing of the expectations between clinical and preclinical medical observers starting from the planning stage of the training programs can provide standardization in the process of development of the oral history taking skill of the students.
Keywords: Educational measurement; clinical competence; medical history taking; medical; education; undergraduate; OBJECTIVITY; CHECKLISTS